Inovasi dan Kolaborasi di Tepi Laut: : Studi Kasus Pengembangan Wisata Malalayang Beach Walk - Johannes, ayu widowati; Fahlevi, Ervin; Natsir, Luthfi Faisal; Santoso, Tina Karini Suciati; Manumpil, Prisilia (Institut Pemerintahan Dalam Negeri (IPDN), 2025)
Malalayang Beach Walk (MBW) not only offers beach tourism but also provides facilities that can be used by the community to enjoy time with family. The location of MBW which is not far from the center of Manado City is the choice of the community to exercise while enjoying the sunset. This study aims to analyze the collaborative governance process according to the theory of Ansell and Gash (2008), this study uses a qualitative method, Data collection techniques are carried out through observation, interviews and documentation. The results of this study indicate that the development of the Malalayang Beach tourist location which was previously conventional, was reorganized by the government with a new face which of course became more beautiful and multi-functional. Innovation and collaboration in the development of MPW tourism have been going well, assessed from various indicators of collaborative governance such as face-to-face dialogue, building trust, commitment to the process has been implemented and proven by each actor, but at the stage of sharing understanding, follow-up is needed by holding meetings between the private sector and the government to get the best solution. Collaborative Governance of the actors in the development of MBW tourism is a strategic effort so that an innovation can run according to expectations, each actor plays a role according to their respective roles.